A Comparative Study of the Effects of the Neurocognitive-Based Model and The Conventional Model on Learner Attention, Working Memory and Mood - Bunterm, Tassanee; Srikoon, Sanit; Nethanomsak, Teerachai; Ngang, Tang Keow (Universiti Utara Malaysia Press, 2017)
Purpose - The attention, working memory, and mood of learners are the most important abilities in the learning process. The importance of these abilities has led the researchers to undertake the present study. This study was concerned with the comparison of contextualized attention, working memory, and mood through a neurocognitive-based model (5P) and a conventional model (5E). It sought to examine the significant change in attention, working memory, and mood of Grade 9 students after the intervention of a neurocognitive-based model (5P) and a conventional model (5E) in an experimental group and a control group, respectively.